Evidence-Based Decision Making in Library Management - Yıldız, Asiye Kakırman (Qualitative and Quantitative Methods in Libraries, 2017)
A fundemental problem of practical sciences such as librarianship is that theory does not always match practice. To put it another way, the idealistic writings in books cannot solve the real problems which are encountered in library management. For this reason, it would be better if managers attempting to solve problems, instead of paying attention to applications which are fashionable in the field of library management and theoretical ideas in books, took decisions with reference to the administrative and economic structure of that particular library. Apart from this, a mistake is often made when  managers take decisions based on their own ideas and judgements or on certain ideologies. These decisions which in the course of the decision-making process are made according to opinions usually lead to loss and failure for the institution. Evidence-based decision making, which is a subject which is relatively new to the field of librarianship, means to use the available data and realities within the existing situation in the best possible way and to stress that a solution which fits one library will not necessarily fit another. In this study, the concept of evidence-based decision making and its importance in library management will be discussed.